Arthrobacter polaris sp. nov., a new cold-adapted member of the family Micrococcaceae isolated from Antarctic fellfield soil. Issue 10 (18th October 2022) - Vodickova, Patricie; Suman, Jachym; Benesova, Eva; Strejcek, Michal; Neumann-Schaal, Meina; Cajthaml, Tomas; Ridl, Jakub; Pajer, Petr; Ulbrich, Pavel; Uhlik, Ondrej; Lipovova, Petra
Abstract : An aerobic, Gram-stain-positive and non-spore-forming strain, designated C1-1 T, was isolated from a fellfield soil sample collected from frost-sorted polygons on Jane Col, Signy Island, Maritime Antarctic. Cells with a size of 0.65–0.9×1.2–1.7 µm have a flagellar motile apparatus and exhibit a rod–coccus growth cycle. Optimal growth conditions were observed at 15–20 °C, pH 7.0 and NaCl concentration up to 0.5 % (w/v) in the medium. The 16S rRNA gene sequence of C1-1 T showed the highest pairwise similarity of 98.77 % to Arthrobacter glacialis NBRC 113092 T . Phylogenetic trees based on the 16S rRNA and whole-genome sequences revealed that strain C1-1 T belongs to the genus Arthrobacter and is most closely related to members of the ' Arthrobacter psychrolactophilus group'. The G+C content of genomic DNA was 58.95 mol%. The original and orthologous average nucleotide identities between strain C1-1 T and A. glacialis NBRC 113092 T were 77.15 % and 77.38 %, respectively. The digital DNA–DNA relatedness values between strain C1-1 T and A. glacialis NBRC 113092 T was 21.6 %. The polar lipid profile was composed mainly of diphosphatidylglycerol, phosphatidylglycerol, phosphatidylinositol and an unidentified glycolipid. The predominant cellular fatty acids were anteiso-C15 : 0 (75 %) and anteiso-C17 : 0 (15.2 %). Menaquinone MK-9(H2 ) (86.4 %) was the major respiratory quinone in strain C1-1 T . The peptidoglycan type was determined as A3α (l -Lys–l -Ala3 ; A11.6). Based on all described phylogenetic, physiological and chemotaxonomic characteristics, we propose that strain C1-1 T (=DSM 112353 T =CCM 9148 T ) is the type strain of a novel species Arthrobacter polaris sp. nov.